Exploration and Analysis of Hidden Fault Identification Methods in the Ordos Basin - Pengfei LI; Yadong ZHANG; Fufeng DING; Peng ZHANG; Zhichun YAO; Xianghu HUANG; Yulong MA (CT Lilun yu yingyong yanjiu, 2024)
Recently, in order to strengthen the exploration and development of oil and gas resources in the Ordos Basin, seismic exploration has changed from a two-dimensional to a three-dimensional (3D) scale. With the progress of 3D seismic processing and interpretation technology, the data quality has improved each year. The Upper Paleozoic faults in the eastern Longdong region are of hidden low sequences with small fault spacings (<5 m); no obvious engineering anomalies exist in most drilling cases. The faults are characterized by distortion and no obvious dislocation in the in-phase axis in the seismic section, which is difficult to identify. Together with the comprehensive analysis of actual drilling and geological knowledge, it was concluded that the faults in this area were prominent in controlling reservoirs and water invasion. Effective identification of the faults in this area is critical in guiding further exploration. At present, the fault identification is based mainly on conventional seismic attributes, such as coherence and curvature; there are some issues, such as large differences in fault attributes, low identification accuracy, and difficulty in determining the duration. The difficulty in identifying hidden faults was solved by means of seismic signal decomposition, forward modeling, residual analysis, amplitude tensor calculation, and section construction constrained by spatial attributes, relying on typical 3D data. The fault identification results using this method are basically consistent with the oil and gas geological knowledge and the actual drilling situation. A preliminary set of methods and technical processes for the identification of hidden faults has been established, which lays a technical foundation for guiding the high-precision identification of faults in similar areas.